A Cooperative Drawing Tool to Improve Children’s Creativity - Ponce Atencio, Yalmar (2019)
Classroom meetings and cooperative homework typically require participants to be physically present in the room. In this setting, the whiteboard is a tool widely used to express ideas. However, nowadays it is more difficult for people to meet together in one place, particularly for young people, due to inherent risks in our current society. Therefore, virtual cooperative applications or tools are welcome. Such tools could reduce the money and time spent on cooperative classwork. Our application allows users to participate virtually through interactive drawings. The features are simple to use and allow for drawings to be made quickly, but this does not mean that drawings cannot be professional or complex. The application was implemented using open source frameworks and libraries, such as NodeJs, SocketIO, PaperJs, jQuery, and others. The results of the experiment demonstrate the high scalability and versatility of our system, the delay is low and acceptable considering that is capable of managing hundreds of objects in real time.